2014
DOI: 10.1093/infdis/jiu625
|View full text |Cite
|
Sign up to set email alerts
|

Cough and the Transmission of Tuberculosis

Abstract: Cough is a predominant feature of respiratory infection and, in tuberculosis, is of prime importance for transmitting infection. Tuberculosis is transmitted by the air, yet the process by which bacilli are aerosolized has received little attention. Features of cough may account for differences in transmission rates from source cases of pulmonary disease. We review the literature on the mechanisms and characteristics of cough in tuberculosis in the context of the dissemination of infection. Coughing is probably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 46 publications
2
78
0
5
Order By: Relevance
“…Among these, cough is regarded as the predominant factor affecting PTB transmission and may be gradually decreased by chemotherapy3334. However, the direct measurement of the human-to-human transmission of PTB is complex and difficult35. Moreover, convincing data on the effectiveness of masks and cough hygiene in reducing PTB transmission are few, although they are widely used protection measures35.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, cough is regarded as the predominant factor affecting PTB transmission and may be gradually decreased by chemotherapy3334. However, the direct measurement of the human-to-human transmission of PTB is complex and difficult35. Moreover, convincing data on the effectiveness of masks and cough hygiene in reducing PTB transmission are few, although they are widely used protection measures35.…”
Section: Discussionmentioning
confidence: 99%
“…Although cough is a well-known hallmark feature of active pulmonary tuberculosis, very little is known about the pathogenesis of infectious cough [17]. Cough may be a natural consequence of lung inflammation and host production of prostaglandins, bradykinin and other inflammatory mediators that activate afferent neuronal C-fibers in the lung mucosa [18].…”
Section: Cough In Tuberculosis Transmissionmentioning
confidence: 99%
“…13,14 Several studies studying cough patterns and household transmission have shown that patients cough more during the day than at night and that cough frequency is an important predictor of transmission. 15,16 As noted by Richard Turner (NHS Foundation Trust, UK), the act of coughing in the context of infectiousness of TB has not been looked into. The cause of cough in a TB patient; its necessity for the transmission of TB, correlation with infective/non-infective strains of the pathogen and characteristics of the optimum cough droplet for disease transmission are yet to be completely understood.…”
Section: Tuberculosis: the Disease The Pathogen And The Hostmentioning
confidence: 99%